1987
DOI: 10.1128/aem.53.12.2983-2986.1987
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Legionella pneumophila by hypochlorite and an organic chloramine

Abstract: The susceptibility of a strain of Legionella pneumophila to disinfection by an organic halamine, free chlorine, and a mixture of the organic halamine and free chlorine was assessed. The organic halamine was found to have superior stability in solution and to exhibit adequate disinfectant potential over a period of 1 month of repeated reinoculations of fresh bacteria. The combined halamine exhibited great potential for use in maintaining closed-cycle cooling water systems free of L. pneumophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Cooling towers have often been implicated as a source for the production of aerosol containing viable legionellae (3). The efficiency of biocidal treatments by chemicals (2,4,(6)(7)(8) and ultraviolet irradiation (10) is known in preventing the growth of legionellae in laboratory studies. To estimate the effects of these treatments, we surveyed microorganisms in coolingtower water during tower operation in summer.…”
mentioning
confidence: 99%
“…Cooling towers have often been implicated as a source for the production of aerosol containing viable legionellae (3). The efficiency of biocidal treatments by chemicals (2,4,(6)(7)(8) and ultraviolet irradiation (10) is known in preventing the growth of legionellae in laboratory studies. To estimate the effects of these treatments, we surveyed microorganisms in coolingtower water during tower operation in summer.…”
mentioning
confidence: 99%
“…Most of the work conducted has involved the assessment of biocidal activity of the compounds rather than investigations of the possible mode of action of these compounds. It has been shown that the halamine disinfectants discussed have a wide range of biocidal activities based on the compound, pH, water quality (high halogen demand versus demand free), temperature, and test organism (15,19,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…The structural feature responsible for the stability of these new N-halamines is the presence of the two methyl groups bonded to the rings adjacent to each nitrogen-halogen bond. The structural formulas for these compounds are shown in reference 10. The efficacies of disinfection for these compounds have been determined for a variety of microorganisms in water at variable pH, temperature, and water quality (9)(10)(11)13). In general the N-chloramine compounds 1 and A tend to require significantly longer contact times at a given total chlorine concentration than does free chlorine to provide sterile water.…”
mentioning
confidence: 99%